Laparoscopic treatment of pediatric paraduodenal hernia in Saudi Arabia - Aisha Gabra; Mohammed H. Ageel (Elsevier, 2022)
Background: Paraduodenal hernia (PDH) is considered the most common type of internal hernia. It accounts for 50% of the internal hernias, which occurs due to failure of the parietal peritoneum to fuse with part of the dorsal mesentery, causing a fossa in the mesocolon. PDH is a rare cause of intestinal obstruction with an unknown incidence in the pediatric population. Case presentation: We present a case of a seven-year-old female patient who presented with non-specific abdominal pain and progressive bilious vomiting for three days. The preoperative diagnosis of the left preduodenal hernia was achieved based on CT findings. The patient underwent laparoscopic repair using a conventional approach. Conclusion: Diagnosis of PDH in pediatric patients requires a high index of suspicion due to the broad spectrum of clinical presentation. Laparoscopic treatment seems to be an efficient and highly effective approach in uncomplicated PDH, resulting in a short length of stay and a fast return to the regular diet.